2015
DOI: 10.1002/dep2.7
|View full text |Cite
|
Sign up to set email alerts
|

Organomineralization processes in freshwater stromatolites: a living example from eastern Patagonia

Abstract: Living stromatolites have been mostly described within shallow marine and (hyper)saline lacustrine environments. Southernmost South America lacks detailed investigations of these (organo)sedimentary buildups, particularly in regions experiencing extreme and variable environmental conditions. Here, we report and describe living freshwater stromatolites in the Maquinchao region, north-western Patagonia, Argentina. Fossil stromatolites characterized by globular and cauliflower shapes are also present in a continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 59 publications
(86 reference statements)
6
39
0
2
Order By: Relevance
“…The XRD and EDS analyses have confirmed that low‐Mg calcite is the main mineral phase of the different morphologies and meso‐structures of the buildups as previously observed by Pacton et al () in the modern stromatolites.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The XRD and EDS analyses have confirmed that low‐Mg calcite is the main mineral phase of the different morphologies and meso‐structures of the buildups as previously observed by Pacton et al () in the modern stromatolites.…”
Section: Resultssupporting
confidence: 83%
“…Pacton et al () have discovered living microbial mats containing low‐Mg calcite, the same mineralogy as in the fossil carbonate buildups. They are only present in the Maquinchao River and absent in both lakes.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations